Web-based approach for systematic analysis and interactive visualization of the industry foundation classes data: a case study in duct design. Issue 3 (4th May 2023) - Deng, Hongxia; Liu, Ying; Liu, Yumeng; Xu, Lei; Wang, Chongen
ABSTRACT: Existing model checkers of building information modeling (BIM) can open industry foundation classes (IFC) files and perform clash detection between mechanical, electrical, and plumbing (MEP) and architectural as well as structural models. However, there are few applications of IFC data in MEP engineering, specifically in interactive visualization between calculation results and BIM models. This study focuses on the systematic analysis of a BIM model and interactive visualization of IFC data for MEP engineering. First, the systematic analysis method for a ventilation system is proposed using the critical path class. Second, referring to the IFC relationship of connections between duct elements, elements in the same system are sorted into different levels of critical paths. Furthermore, ifcPressureViewer is developed based on the interactive visualization methodology by connecting Three.js, a JavaScript 3D library, with Echarts, a JavaScript visualization library, which is applicable for desktop computers and mobile tablets. This is followed by a case study that demonstrates the application of the interactive visualization process. Finally, the conclusions of this study are summarized, and directions for future research are discussed. GRAPHICAL ABSTRACT: uf0001